Impacts of implementing geogebra on eleventh grade student’s learning of Euclidean Geometry - Bayaga, A.; Mthethwa, M.M.; Bossé, M.J.; Williams, D. (South African Journal of Higher Education, 2020)
The aim of the study was to evaluate the efficiency of applying GeoGebra software as a teaching tool to enhance high poverty, rural grade 11 students’ understanding of Euclidean geometry circle theorems. The experimental group received instruction on how to use, make simple constructions, and measure elements in GeoGebra. The control group was taught in a traditional lecture method. Using a quantitative research design, the findings indicated that the use of GeoGebra had a statistically significant effect on the students’ ability to correctly complete problems regarding some circle geometry theorems. Additionally, using a Likert scored questionnaire, students demonstrated that they valued the use of GeoGebra and appreciated this learning innovation. Altogether, students who interacted with GeoGebra were highly engaged in the learning processes and actively collaborated with other students rather than remaining passive learners. The students who participated in the study evaluated GeoGebra as an appropriate tool to assist them in the learning of mathematics.